Analysis of the Effects of Economic Policy on Car Demand in Indonesia - Muh. Zuhal Zainal (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2021)
This study is aims to analyze and to find out the impact of economy policy for demand for cars in Indonesia. The variables consist of this study such as GDP per capita, length of road, price of fuel, interest rate for credit consumption and demand for cars. This study uses the secondary data through the Central Bureau of Statistics analyzed by multiple linear regression and Eviews 8 programs. The results showed that R Square value of 0.994, which means that 99% of demand for cars is jointly influenced by variables in the model. While the remaining is influenced by other factors outside the model. The partial result shows the GDP per capita has not affect, length of road gives a positive affect and significant, BBM price gives a positive affect and significant